Age-modified and point-modified intracerebral hemorrhage (ICH) scores are more reliable alternatives to the original ICH score for Indonesian patients: A retrospective cohort study at a tertiary center in Indonesia - Aloysius Bagus Sasongko; Petra Octavian Perdana Wahjoepramono; Danny Halim; Kurnia Wahyudi; Achmad Adam; Yeo Tseng Tsai; Julius July; Eka Julianta Wahjoepramono; Tri Hanggono Achmad (World Neurosurgery: X)
Background: Specific regional epidemiological characteristics may influence the reliability of the ICH score. This study aims to evaluate the application of the original ICH score in Indonesian patients and subsequently assess potential modifications to enhance its applicability. Methods: The ICH score of each patient admitted to a tertiary center in Indonesia was assessed. Based on the average age of ICH in Indonesian patients and their life expectancy, the age threshold was modified to 59 years. Statistical analyses were then conducted to evaluate the association between the variables in both the original and age-modified ICH scores and in-hospital mortality. Based on the strength of the association of each variable with ICH patient mortality, potential modifications to the point values for each variable in predicting ICH patient mortality were tested. Results: This study included 225 ICH patients. As many as 185 ICH patients (82.2 %) survived the ordeal. Contrary to the findings that formulated the original ICH score, only the admission GCS (p < 0.001), ICH volume (p < 0.001), and IVH (p < 0.001) are significantly associated with in-hospital mortality; meanwhile, age and infratentorial ICH origin are not. Modifying the age threshold from 80 years (p = 0.546) to 59 years (p = 0.095) strengthened the association between age and mortality. Point modifications in the original and age-modified ICH scores suggested new cumulative scores of 24 and 26, respectively. Conclusions: Fifty-nine years is a more appropriate threshold for the age variable in the ICH score for Indonesian patients. Interestingly, not all variables within the ICH scores are significant; therefore, a new set of scores is recommended.